Increased Student Learning Outcomes at Colloidal Materials Integrated Islamic Values Through the Scientific Approach - Arofah, Barorotul Ulfah; Cahyono, Edy; Wijayati, Nanik (Journal of Innovative Science Education, 2018)
The development of the current educational system, has focused integralistly that removes barriers between science and religion. But there are still many Islamic school that have not yet integrated the values of Islam in learning, so it is necessary to use a certain approach. Learning through a scientific approach has a very strategic role in improving student learning outcomes. The purpose of this research is to know and describe the improvement of student learning outcomes in the learning of colloidal chemistry integrated Islamic values through scientific approach. This research uses experimental method, with pretest and posttest control group design design. The results showed that there was an increase in learning outcomes in the control and experimental classes altogether in the low improvement category, but the improvement in both quality / statistics was no significant difference. The percentage increase in the experimental class (10.1%) was greater than the control class (5.5%). The conclusion in this research is the study of integrated colloidal chemistry of Islam through scientific approach can improve student learning outcomes.